Glacier-Wide Mass Balance and Compiled Data Inputs: USGS Benchmark Glaciers ... - U.S. Geological Survey Benchmark Glacier Program; Christopher J. Mcneil; Louis Sass; Caitlyn E Florentine; Emily H Baker; Erich H Peitzsch; Erin N Whorton; Zachary S Miller; Daniel B Fagre; Adam M Clark; Shad R O'Neel; Katherine E Bollen (U.S. Geological Survey, 2016)
Since the late 1950s, the USGS has maintained a long-term glacier mass-balance program at key North American glaciers. Measurements began on South Cascade Glacier, WA in 1958, expanding to Gulkana and Wolverine glaciers, AK in 1966, and later Sperry Glacier, MT in 2005. The Juneau Icefield Research Program has measured glacier mass balance on Lemon Creek since the mid-1940s, with USGS providing complimentary seasonal measurements of Lemon Creek beginning in 2014 (JIRP; McNeil et al., 2020). Direct field measurements of point glaciological data are combined with weather and geodetic data to estimate the seasonal and annual mass balance at each glacier in both a conventional and reference surface format (Cogley and others, 2011). The analysis framework (O'Neel and others, 2019; Florentine and others, 2024; prior to v 3.0 van Beusekom and others, 2010) is identical at each glacier to enable cross-comparison between output time series. Vocabulary used follows Cogley and others (2011) Glossary of Glacier Mass ...